Numerical simulation of the blast-resistant response of ultrahigh-performance concrete structural members - Yin, Hor; Shirai, Kazutaka; Teo, Wee (Journal of Civil Engineering and Management, 2019)
This paper presents the blast responses of ultrahigh-performance concrete (UHPC) structural members obtained using finite element (FE) modelling. The FE model was developed using LS-DYNA with an explicit solver. In the FE simulation, the concrete damage model, which is a plasticity-based constitutive material model, was employed for the concrete material. The simulation results were verified against previous experimental results available in the literature and were shown to be in good agreement with the experimental results. In addition, the developed FE model was implemented in a parametric study by varying the blast weight charges. The numerical results for UHPC members were compared with those for conventional reinforced concrete (RC) members. The numerical responses, such as the maximum deflections, deflected shapes, and damage patterns, of the UHPC members subjected to blast loading were significantly better performance than those of the RC members as a result of the high strength and ductile capacity of UHPC.